Iron kinetics following treatment with sucroferric oxyhydroxide or ferric citrate in healthy rats and models of anaemia, iron overload or inflammation. Issue 6 (7th April 2020) - Floege, Jürgen; Funk, Felix; Ketteler, Markus; Rastogi, Anjay; Walpen, Sebastian; Covic, Adrian C; Sprague, Stuart M
Abstract: Background: The iron-based phosphate binders, sucroferric oxyhydroxide (SFOH) and ferric citrate (FC), effectively lower serum phosphorus in clinical studies, but gastrointestinal iron absorption from these agents appears to differ. We compared iron uptake and tissue accumulation during treatment with SFOH or FC using experimental rat models. Methods: Iron uptake was evaluated during an 8-h period following oral administration of SFOH, FC, ferrous sulphate (oral iron supplement) or control (methylcellulose vehicle) in rat models of anaemia, iron overload and inflammation. A 13-week study evaluated the effects of SFOH and FC on iron accumulation in different organs. Results: In the pharmacokinetic experiments, there was a minimal increase in serum iron with SFOH versus control during the 8-h post-treatment period in the iron overload and inflammation rat models, whereas a moderate increase was observed in the anaemia model. Significantly greater increases (P < 0.05) in serum iron were observed with FC versus SFOH in the rat models of anaemia and inflammation. In the 13-week iron accumulation study, total liver iron content was significantly higher in rats receiving FC versus SFOH (P < 0.01), whereas liver iron content did not differ between rats in the SFOH and control groups. Conclusions: Iron uptake was higher from FC versus SFOH following a single dose in anaemia, iron overload and inflammation rat models and 13 weeks of treatment in normal rats. These observations likely relate to different physicochemical properties of SFOH and FC and suggest distinct mechanisms of iron absorption from these two phosphate binders.